Contrasting Patterns of Agonist-induced Store-operated Ca2+ Entry and Vasoconstriction in Mesenteric Arteries and Aorta With Aging. Issue 6 (June 2015) - Yang, Yong; Zhu, Jinhang; Wang, Xia; Xue, Nairui; Du, Juan; Meng, Xiangling; Shen, Bing
Abstract : Abstract: Ca 2+ is a crucial factor in the regulation of smooth muscle contraction. Store-operated Ca 2+ entry (SOCE) is one pathway that mediates Ca 2+ influx and smooth muscle contraction. Vessel contraction function usually alters with aging to cause severe vascular-related diseases. However, the underlying mechanism is still not fully understood. Here, we assessed intracellular Ca 2+ and vessel tension and found that SOCE and SOCE-mediated contraction of vascular smooth muscle cells (VSMCs) was reduced in aorta but increased in mesenteric arteries from aged rats. The results of Western blot and immunofluorescence staining show that the expression levels of Orai1, a store-operated Ca 2+ channel, were increased in VSMCs of mesenteric arteries but were reduced in VSMCs of aorta with aging. In conclusion, we demonstrated that the changing pattern of SOCE and SOCE-mediated contraction of VSMCs is completely reversed in mesenteric arteries and aorta with aging, providing a potential therapeutic target for clinical treatment in age-related vascular diseases.